Morphological, Biochemical, and Cytological Analyses of Deep-Sowing Tolerance in Sorghum Seeds - Yutao Huang; Zhaotong You; Heyun Chen; Xiuhui Liu; Gaofu Mei; Heqin Liu; Dongdong Cao; Xueqiang Zheng; Guihua Zou (Plants)
Deep-sowing tolerance (DST) is a key trait for the field germination of sorghum (Sorghum bicolor L.) seeds, especially in arid and semi-arid regions. However, the mechanisms of DST are poorly understood in sorghum. In this study, we compared two sorghum lines with contrasting tolerance to deep sowing for morphological, biochemical, and cytological changes during germination from deep soil (15 cm). The deep-sowing-tolerant (DT) line (Daluochui) showed 79% seedlings establishment (SE), while the deep-sowing-sensitive (DS) line (Xiaobailiang) showed no established seedlings at 7 days after sowing. Mesocotyl elongation is a key morphological change that accounted for the difference in seedling establishment between DT and DS. The mesocotyl elongation in DT was jointly established by both cell division and expansion. The levels of ethylene, auxin, and spermidine were markedly higher in DT than DS and were also supported by enzyme activity and qPCR, indicating that phytohormones play an important role in seed emergence from deep soil. Furthermore, α-amylose activity, soluble sugar, and ATP contents in DT were markedly higher than in DS, suggesting that there was a better energy supply in DT during deep-sowing emergence. The activities of endo-1,4-β-xylanase and endo-β-mannanase, as well as the expression of the corresponding genes, were higher in DT than DS. This study identified potential key regulatory factors that may control sorghum DST and yield potential, thus, providing new insights into the molecular mechanism of sorghum DST.